Pengaruh Pelatihan dan Pengembangan Karir terhadap Kinerja Karyawan Bank Central Asia KCP Kalimalang 1 Jakarta Timur - Pertiwi , Anggraheni Puspa; Dwi Syahputra, Arry (Program Studi Magister Manajemen Fakultas Ekonomi Universitas Krisnadwipayana, 2026)
The purpose to analyze the influence of training and career development on employee performance at BCA KCP Kalimalang 1 Jakarta Timur. This research is included in the category of causal associative research using a quantitative approach. The population in this study were all 30 employees of BCA KCP Kalimalang 1 Jakarta Timur. The sampling technique uses a saturated sampling technique, where all members of the population are sampled. The analytical method uses simultaneous and partially linear regression analysis. The results showed that in simultaneous or partially ways the training and career development have a positive and significant on employee performance at BCA KCP Kalimalang 1 Jakarta Timur.